1982
DOI: 10.1139/b82-169
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cellular amino acids, protein, and total organic nitrogen during fruitbody development in Flammulina velutipes. I. Growth on sawdust medium

Abstract: Dry weights of stipes and pilei of Flammulina velutipes grown on nutrient-supplemented sawdust increased throughout the growth period. The pilei weighed only slightly less than the stipes. Amounts of total organic nitrogen, α-amino nitrogen, and alkali-soluble protein increased in the whole pileus and stipe as the fruitbodies elongated, but the concentrations on a dry weight basis decreased although they were always highest in the pileus. The concentration of alkali-insoluble nitrogen increased in both structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
3

Year Published

1982
1982
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 0 publications
3
13
0
3
Order By: Relevance
“…Similarly, magnesium, phosphorous and potassium were found to be more preponderant in the pilei than stipes (Tables 2 and 3). These findings are in agreement with those of MOORE et al [lo], and GRUEN et al [4] who found the pileus to be a greater storage depot than the stipe of Coprinus fagopus, Macrolepwta procera and F l a~~u l i~ velutipes. However the observed presence of higher crude fibre and calciumcontents in the stipes of both L. subnudus and T. robustus presumably may be to strengthen the stipe for mechanical support of the pileus (Tables 2 and 3).…”
Section: Resultssupporting
confidence: 93%
“…Similarly, magnesium, phosphorous and potassium were found to be more preponderant in the pilei than stipes (Tables 2 and 3). These findings are in agreement with those of MOORE et al [lo], and GRUEN et al [4] who found the pileus to be a greater storage depot than the stipe of Coprinus fagopus, Macrolepwta procera and F l a~~u l i~ velutipes. However the observed presence of higher crude fibre and calciumcontents in the stipes of both L. subnudus and T. robustus presumably may be to strengthen the stipe for mechanical support of the pileus (Tables 2 and 3).…”
Section: Resultssupporting
confidence: 93%
“…[13] for Macrolepiota proceru, CHANG et al [4] for V. volvacea, GRUEN et al [8] The presence of more food nutrients in the pilei than the stipes is likely to be due to the pileus acting as a strong metabolic force which draws materials continuously from the substrate through the stipe during sporophore development. GRUEN et al [9] found that radioactive materials are moved from the substrate into the pileus through the stipe.…”
Section: Resultsmentioning
confidence: 99%
“…After sequential extraction with 80% ethanol, ice-cold 5% trichloroacetic acid, and 1 M NaOH, the alkali-soluble protein was measured by the method of Lowry et al (1951) ethanol, hydrolysis of the residue, and purification on resin columns yielded free and protein amino acids, which were analyzed quantitatively with a Technicon TSM-1 R amino acid analyzer. Details of the various procedures were reported previously (Gruen and Wong 1982). For determination of total organic nitrogen in pooled culture medium only small volumes (0.20-0.25 mL) were used for micro-Kjeldahl analysis at each time interval because carbohydrates caused excessive frothing during digestion with H2SO4.…”
Section: Extraction and Analysis Of Nitrogen Compoundsmentioning
confidence: 99%
“…SFB, VM, and stipes and pilei of LFB (30-day cultures) were freeze-dried and the nitrogenous fractions were extracted and separated as described previously (Gruen and Wong 1982) except that whole fruitbodies and VM were homogenized twice in 10 mL of 80% ethanol for 2 min each with a Soma11 omnimixer. Radiochemically pure L-[U14C]leucine (lot No.…”
Section: Radioisotope Experimentsmentioning
confidence: 99%
See 1 more Smart Citation